Interlaboratory reproducibility of a touch-transfer assay for the assessment of antimicrobial surfaces. (April 2023) - Mayr, A.; Knobloch, J.K.; Hinterberger, G.; Seewald, V.; Wille, I.; Kaltseis, J.; Knobling, B.; Klupp, E.-M.T.; Samardzic, E.; Lass-Flörl, C.
Summary: Background: Various assay methods have been developed to study antimicrobial activity based on contamination of surfaces with different amounts of liquid bacterial suspensions. Since surfaces with frequent hand contact are typically touched in a dry state in clinical settings, these tests may be inappropriate at assessing effectiveness to reduce pathogen transmission. Aim: To investigate a surface previously confirmed to display antimicrobial activity even after drying of small volumes of bacterial suspension (Egger antimicrobial surfaces: EAS) under conditions modelling dry contamination using a touch-transfer method. Methods: EAS, an antimicrobial copper alloy, as well as a negative control were examined to assess interlaboratory test reproducibility. Findings: Significantly fewer bacteria on EAS after touch transfer and some differences in the touch transmission were detected between the two laboratories. However, an identical assessment of effectiveness for EAS came from both laboratories. Interestingly, despite previously detected antimicrobial efficacy of EAS and the antimicrobial copper alloy after liquid contamination, insufficient activity was observed under dry conditions during a contact time of 4 h by both laboratories. Experiments under standardized air humidity in one laboratory revealed at least for copper a strong influence of humidity on antimicrobial activity. These data indicate that procedures involving contamination of surfaces with organisms suspended in liquids are not directly comparable to dry contamination. Conclusion: Since, in the real world of a hospital, organisms are typically transferred between dry surfaces, further standardization of the touch-transfer method is worthwhile for a better understanding of the efficacy of such surfaces.